(untitled) (Comprehensive Journal of Science, 2026)
The generators of olives are important centers in olive oil production, as training practices in them affect the product’s best and consumer protection. This study, as randomly targeted the evaluation of (five) olive turbines in the metropolis in Tarhuna city- Libya, used specific standards with place, buildings, fruit handling, fitness inspection, corridors, equipment, water, laboratory, staff, toilets, toilets, liquid waste and packaging. Effects uncovered variation in adherence to health standards, compliance quotes between 30.29% and 48.9%. It was observed in the assessment that the highest lined factory number (1) became extraordinary, which became extraordinary in terms of total score (48.9 %), followed by mill number (five) (45.8 %). In contrast, the weakest generator factories (4) were the lowest assessment (30.29%), which was seen by Mills (3) and (2). Inspection confirmed a clear weakness in important components with fitness inspection, the availability of laboratories and packaging, and emphasized the pressure to improve fitness conditions in turbines. This is a look that aims to assess fitness conditions in 5 olive turbines in the city of Tarhuna, Libya.